2021
DOI: 10.1177/11795735211048045
|View full text |Cite
|
Sign up to set email alerts
|

Channelopathy of Dravet Syndrome and Potential Neuroprotective Effects of Cannabidiol

Abstract: Dravet syndrome (DS) is a channelopathy, neurodevelopmental, epileptic encephalopathy characterized by seizures, developmental delay, and cognitive impairment that includes susceptibility to thermally induced seizures, spontaneous seizures, ataxia, circadian rhythm and sleep disorders, autistic-like behaviors, and premature death. More than 80% of DS cases are linked to mutations in genes which encode voltage-gated sodium channel subunits, SCN1A and SCN1B, which encode the Nav1.1α subunit and Nav1.1β1 subunit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 182 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…It is clear that DS predominantly arises from diminished NaV1.1 functionality due to haploinsufficiency. Mutations in the SCN1A gene disrupt the balance between neuronal excitation and inhibition in the brain, leading to epileptic seizures and other symptoms of DS [25]. Electrophysiological scrutiny of DS-linked missense variants underscores their tendency to provoke loss-of-function alterations, often rendering channels nonfunctional.…”
Section: Physiopathology Of Scn1a In Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that DS predominantly arises from diminished NaV1.1 functionality due to haploinsufficiency. Mutations in the SCN1A gene disrupt the balance between neuronal excitation and inhibition in the brain, leading to epileptic seizures and other symptoms of DS [25]. Electrophysiological scrutiny of DS-linked missense variants underscores their tendency to provoke loss-of-function alterations, often rendering channels nonfunctional.…”
Section: Physiopathology Of Scn1a In Dsmentioning
confidence: 99%
“…CBD is a non-psychoactive compound derived from cannabis plants. Several studies [25,98], have reported that CBD use led to a significant reduction in seizure frequency in patients with DS. CBD is believed to exert its antiepileptic effects through multiple mechanisms, including modulation of neuronal excitability and inflammation.…”
Section: Cannabidiolmentioning
confidence: 99%
“…Xu et al summarized evidence on the direct and indirect mechanisms of action of sodium, potassium, and HCN channels in Dravet syndrome and understanding the application of CBD, whose antiepileptic effects enable modulation of these channels [ 103 ]. CBD has demonstrated neuroprotective effects in experimental animal models of Dravet syndrome as well as clinical data.…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
“…Despite advances in understanding the genetic and molecular basis of DS, there is still no cure for the condition, and current treatment options focus on seizure control and management of associated symptoms (8,24). Conventional antiepileptic drugs (AEDs) are often ineffective in controlling seizures in individuals with DS, and multiple drug therapies, such as a combination of sodium channel blockers and other AEDs, are often required (8,25).…”
Section: Introductionmentioning
confidence: 99%